(untitled) (Journal of Academic Finance, 2019)
T The emergence of a new current of research, behavioral finance, linking market behavior and human psychology, aims to study the cognitive biases related to investor behavior that are not explained by the traditional theory of finance. Our empirical study focuses, firstly, on the identification of the stock market crises that affected the Tunis Stock Exchange during the period from 1998 to 2018 and, secondly, on the measure of investor sentiment in the Tunisian market. We check that the indicator of sentiment of the investor agrees with the stock market crises and we find that the sentiment of the investor causes the Tunisian stock market crises in the sense of Granger. Hence, new proof is made of the important role played by investors in the transmission of stock market crises.